Использование аксиологического подхода как условие эффективности этнокультурного образования будущих педагогов - Таженова, Г.Б. (My University, 2016)
This article considers the main issues of human values realization in ethnopedagogy education. The axiological approach is the most fundamental in the methodological ethnopedagogy. The human values are declared and are not used in the modern educational practice. According to the author’s opinion usage of ethnopedagogical materials by preparation of the future specialists has led to development of common culture and spirituality of the future teachers. It is important in education of younger generation.
Keywords: ethnopedagogy; axiological approach; human values; professional education; content of education